COVID-19: economic aspects of inﬂuenza vaccine prevention - E. A. Zhidkova; E. M. Gutor; Yu. A. Tkachenko; I. V. Rogova; I. A. Popova; K. G. Gurevich (Izdatelstvo OKI, 2021)
Relevance. A viral pandemic caused by the SARS-CoV-2 coronavirus has led to the development of a new coronavirus disease-2019 (COVID-19). The COVID-19 pandemic has forced the mobilization of all available health system resources. There are separate publications on reducing the risk of developing coronavirus infection in people vaccinated against influenza. Objective: to study the cost-effectiveness of influenza vaccination in the conditions of the» first « wave of COVID-19. Materials and methods. The archival data of 2,452 people from among the sick employees of JSC «Russian Railways» were analyzed. The control group consisted of 2,911 employees who were not infected with COVID-19, comparable by gender, age and territory of residence. Scores on the Charlson comorbidity scale were calculated for all individuals. The pharmacoeconomical cost of the patient's treatment was predicted using the Markov model. Results. Having a flu shot reduced the likelihood of getting COVID-19 by 1.3 times. In the presence of a diagnosis of coronavirus infection, inpatient treatment for influenza vaccinated patients was required 2 times less often than for unvaccinated patients. Compared to the situation of the absence of vaccinated persons, in the «first wave», the estimated cost savings for the treatment of patients with coronavirus infection amounted to 124 million rubles. When the number of points on the comorbidity scale increased from 1 to 8, the average cost of treatment of patients without previous influenza vaccination increased by 2 times, and in the presence of vaccination, the average cost of treatment increased by 1.7 times. Conclusion. Thus, this study shows that influenza vaccination is cost-effective against COVID-19. The effect is achieved by reducing the likelihood of getting a coronavirus infection in the presence of a flu shot.